Resistance differences of representative model microorganisms in different disinfection processes: ZIF-67, UVC and ozone - Xiang Zheng; Qingwen Yang; Jincheng Xia; Rong Cheng; Haiyan Li; Jianzhong Zheng (Water Cycle)
Due to their inherent nature, each type of microorganism exhibits unique resistance to various disinfection processes. Disinfection with nanomaterials represents a promising technology that has garnered significant interest. Among them, ZIF material has antibacterial and antiviral activities, and ZIF-67 material is a new type of nanomaterial that can effectively kill bacteria and viruses, with the potential for large-scale use. Therefore, in this paper, we investigate the differences between nanomaterial disinfection techniques (employing ZIF-67) and traditional inactivation techniques (e.g., ultraviolet-C and ozone). Phage MS2 and PhiX174 and their respective host E. coli were chosen as the representative microorganisms. Our findings indicate that phages exhibit greater resistance to ZIF-67 and traditional disinfection techniques than bacteria, but different techniques show specific disinfection effects on the three disinfection microorganisms. Considering the differences, choosing appropriate disinfection techniques based on the characteristics of the disinfected substances in practical disinfection technology selection is essential.